2020
DOI: 10.1111/jfbc.13534
|View full text |Cite|
|
Sign up to set email alerts
|

Novel antihypertensive action of rutin is mediated via inhibition of angiotensin converting enzyme/mineralocorticoid receptor/angiotensin 2 type 1 receptor (ATR1) signaling pathways in uninephrectomized hypertensive rats

Abstract: Hypertension is the most common cardiovascular disease that affects approximately 26% of adult population, worldwide. Rutin is one of the important flavonoids that is consumed in the daily diet, and found in many food items, vegetables, and beverages. Uninephrectomy (UNX) of the left kidney was performed, followed by induction of hypertension. The rats were randomly divided into four groups of 10 rats: group 1-Sham-operated rats; group 2-UNX rats, group 3-UNX-L-NAME (40 mg/ kg) plus rutin (100 mg/kg bwt), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Rutin is a common flavonoid with significant pharmacological activity. It can inhibit angiotensin converting enzyme (ACE), angiotensin 2 type 1 receptor (ATR1) and mineralocorticoid receptor (MCR) to play a protective and therapeutic role in cardiovascular diseases [ 31 ]. Therefore, the above seven components were selected as markers to reflect the pharmacokinetic study of oral salvia miltiorrhiza stem-leaf in rats, in order to provide a reference for the absorption, distribution, metabolism and excretion process of Salvia miltiorrhiza stem-leaf in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Rutin is a common flavonoid with significant pharmacological activity. It can inhibit angiotensin converting enzyme (ACE), angiotensin 2 type 1 receptor (ATR1) and mineralocorticoid receptor (MCR) to play a protective and therapeutic role in cardiovascular diseases [ 31 ]. Therefore, the above seven components were selected as markers to reflect the pharmacokinetic study of oral salvia miltiorrhiza stem-leaf in rats, in order to provide a reference for the absorption, distribution, metabolism and excretion process of Salvia miltiorrhiza stem-leaf in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…However, rutin administration exhibits suppression of ACE I activity, activation of ACE II, and down-regulations of B1R and B2R protein expressions in the kidney tissues of IRR-, MT-, and IRR/MT-intoxicated animals; thus, rutin can prevent Ang II accumulation in the kidney tissues that further regulates renal hypertension. Rutin demonstrates antihypertensive properties in a mechanism comprising ACE I suppression (Oyagbemi et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the blood pressure‐lowering effect of the extract was comparable to that of a 40 mg/kg bw valsartan (Yao et al., 2021), suggesting that litchi seed has a strong potential to reduce vasoconstriction and hypertension. Chromatographic analysis showed that the extracts were rich in gallic acid and flavonoids, such as procyanidins, quercetin, rutin, catechin, and epicatechin (Kessy et al., 2018; Yao et al., 2021), which have been reported to exhibit inhibitory action on angiotensin I‐converting enzyme (Actis‐Goretta et al., 2003; Häckl et al., 2002; Jin et al., 2017; Oyagbemi et al., 2020; Takagaki & Nanjo, 2015).…”
Section: Pharmacological Phytochemical and Toxicological Aspects Of Litchi Fruit Seed And Peelmentioning
confidence: 99%